Recent Advances in the Synthesis of Peptoid Macrocycles. Issue 30 (21st February 2018) - Webster, Alexandra M.; Cobb, Steven L.
Abstract: Over the past two decades, developing medical applications for peptides has, and continues to be a highly active area of research. At present there are over 60 peptide‐based drugs on the market and more than 140 in various stages of clinical trials. The interest in peptide‐based therapeutics arises from their biocompatibility and their ability to form defined secondary and tertiary structures, resulting in a high selectivity for complex targets. However, there are significant challenges associated with the development of peptide‐based therapeutics, namely peptides are readily metabolised in vivo. Peptoids are an emerging class of peptidomimetic and they offer an alternative to peptides. Peptoids are comprised of N‐substituted glycines where side‐chains are located on the nitrogen atom of the amide backbone rather than the α‐carbon as is the case in peptides. This change in structure confers a high degree of resistance to proteolytic degradation but the absence of any backbone hydrogen bonding means that peptoids exhibit a high degree of conformational flexibility. Cyclisation has been explored as one possible route to rigidify peptoid structures, making them more selective, and, therefore more desirable as potential therapeutics. This review outlines the various strategies that have been developed over the last decade to access new types of macrocyclic peptoids. Abstract : Macrocyclic peptoids : Developing medical applications for peptides has, and continues to be a highly active area of research. However, there are significant challenges associated with the development of peptide‐based therapeutics. Peptoids offer an alternative to peptides but the absence of any backbone hydrogen bonding means they exhibit a high degree of conformational flexibility. Cyclisation has been explored as one possible route to rigidify peptoid structures. This review outlines the recent strategies that have been developed to access new types of macrocyclic peptoids.